Determinants of Short- and Long-Term Commercial Lending Rates in Peru, 2010–2022 - Bravo Orellana, Sergio (2023)
Short- and long-term interest rates are crucial for investment and, thus, business dynamism. The injection of money depends on the ability to promote cash flows through credit which boosts productive sectors. In the last decade, among Latin American countries, Peru has stood out for its key financial system and macroeconomic stability characteristics. The Central Reserve Bank of Peru (BCRP) plays a key role in setting the reference rate given its autonomy and strong institutional trust. However, the mixed pension system injects liquidity into the financial system through its private contributions. For the purposes of this study, an autoregressive econometric model of distributed lags (ARDL) was employed. The findings reveal that the reference rate set by the BCRP establishes a long-term relationship for both short and long-term rates, empirically demonstrating the effectiveness of monetary policy. Additionally, the liquidity provided by the pension system triggers an immediate shock response in determining the short-term rate. It is also observed that the issuance of sovereign bonds is a robust tool in determining the long-term rate due to its facilitation of credit access. This research is relevant for identifying macroeconomic and financial variables and guiding the formulation of macroeconomic policies.